Management of water conservation through irrigation system modernization and rehabilitation - Dimmitt, A. K., author; McLaughin, K. I., author; Kamand, F. Z., author; Welch, D. G., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1992)
A landmark water conservation agreement became effective in December 1989 between the Metropolitan Water District of Southern California and Imperial Irrigation District to conserve 106,110 acre-feet of water annually through the modernization and rehabilitation of Imperial Irrigation District's irrigation distribution system. The agreement provides for 17 projects (Program) to be planned, designed and implemented over a five year period, ending in 1995, plus verifying project accomplishments both from a cost and volume of water conserved standpoint. Management of the planning, design and implementation process, the process of verifying project accomplishments and three case studies demonstrating the various planning approaches used are presented.
Irrigation and water resources in the 1990's
Conservation by modernization and rehabilitation
Not digitized by CSUL Digital Services.
Presented at Irrigation and water resources in the 1990's: proceedings from the 1992 national conference held on October 5-7, 1992 in Phoenix, Arizona.